2014
DOI: 10.7554/elife.03751
|View full text |Cite
|
Sign up to set email alerts
|

A kinase-independent function of AKT promotes cancer cell survival

Abstract: The serine–threonine kinase AKT regulates proliferation and survival by phosphorylating a network of protein substrates. In this study, we describe a kinase-independent function of AKT. In cancer cells harboring gain-of-function alterations in MET, HER2, or Phosphatidyl-Inositol-3-Kinase (PI3K), catalytically inactive AKT (K179M) protected from drug induced cell death in a PH-domain dependent manner. An AKT kinase domain mutant found in human melanoma (G161V) lacked enzymatic activity in vitro and in AKT1/AKT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
69
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 23 publications
4
69
1
1
Order By: Relevance
“…Our laboratory and others have shown that ATP-competitive (GSK690693, GDC0068, AZD5363) and allosteric antagonists of AKT (MK-2206) inhibit AKT kinase activity in dose dependent fashion as determined by phosphorylation of AKT substrates in multiple tumor cells including melanoma, breast and lung cancer (4). Vivanco et al (5) reported a PH domain-dependent, kinase-independent function of AKT associated with cancer cell survival. In the same study a comparison of MK-2206 with the ATP-competitive inhibitors GSK690693 and GDC0068 showed that the latter induce less cell death than MK-2206 despite greater inhibition of phosphorylation of AKT substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory and others have shown that ATP-competitive (GSK690693, GDC0068, AZD5363) and allosteric antagonists of AKT (MK-2206) inhibit AKT kinase activity in dose dependent fashion as determined by phosphorylation of AKT substrates in multiple tumor cells including melanoma, breast and lung cancer (4). Vivanco et al (5) reported a PH domain-dependent, kinase-independent function of AKT associated with cancer cell survival. In the same study a comparison of MK-2206 with the ATP-competitive inhibitors GSK690693 and GDC0068 showed that the latter induce less cell death than MK-2206 despite greater inhibition of phosphorylation of AKT substrates.…”
mentioning
confidence: 99%
“…This can be explained in part by structural studies demonstrating that allosteric inhibitors lock AKT in a closed conformation with its phospholipid binding site blocked by the kinase domain (6). In stark contrast, cells treated with ATP-mimetics displayed increased binding of AKT to PtdIns(3,4)P2 (PIP2) and PtdIns(3,4,5)P3 (PIP3) and increased localization of AKT at the plasma membrane, resulting in its hyperphosphorylation at the PDK1 site T308 and the mTORC2 site S473 (5). Thus, ATP-competitive AKT inhibitors promote membrane localization of AKT and fail to block its kinase-independent function, liabilities that may limit their effectiveness compared to allosteric inhibitors.…”
mentioning
confidence: 99%
“…These results strongly suggest that TXNIP physically interacts with AKT in cells in a glucose‐dependent manner. Next, we constructed site‐directed mutants of AKT for kinase activity‐related residues including catalytically inactive AKT (K179M) and AKT mutants with active phosphorylation sites (T308A, S473A, or T308A/S473A) (Vivanco et al, 2014). As shown in Supporting Information Figure S3C,D, the interaction between TXNIP and AKT was not affected by AKT kinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a novel kinase-independent Akt pathway was discovered (80). When the Akt kinase domain is inactivated, Akt can resist a hostile environment through another domain of the Akt protein, which is named PH domain.…”
Section: Pathways Involved In the Self-renewal Of Ccscsmentioning
confidence: 99%